Probing Jovian Broadband Kilometric Radio Sources Tied to the Ultraviolet Main Auroral Oval With Juno. Issue 2 (24th January 2019) - Imai, Masafumi; Greathouse, Thomas K.; Kurth, William S.; Gladstone, G. Randall; Louis, Corentin K.; Zarka, Philippe; Bolton, Scott J.; Connerney, John E. P.
Abstract: Observations of Jovian broadband kilometric (bKOM) radiation and ultraviolet (UV) auroras were acquired with the Waves and Juno‐UVS instruments for ∼2 hr over the northern and southern polar regions during Juno's perijoves 4, 5, and 6 passes (PJ4, PJ5, and PJ6). During all six time periods, Juno traversed auroral magnetic field lines connecting to the UV main auroral ovals, matching the estimates of bKOM radio source footprints. The localized bKOM radio sources for the PJ4 north pass map to magnetic field lines having distances of 10 to 12 Jovian radii ( R J ) at the magnetic equator, whereas the extended bKOM radio sources for the other events map to field lines extending to 20–61 R J . We found the peak bKOM intensities during Juno's potential radio source crossings show positive, negative, and no correlations with the UV main oval brightness and color ratio. Only the positive correlations suggest wave‐particle energy transport. Plain Language Summary: Jupiter's polar auroras show complex emissions at radio and ultraviolet (UV) wavelengths. However, understanding these two phenomena and how they interact has been hindered by poor visibility of these observations from Earth or near‐equator spacecraft and insufficient spatial resolution of the Jovian radio images. Since 5 July 2016, the Juno spacecraft has toured Jupiter as its first polar explorer in a 53‐day eccentric orbit. One of Juno's main goals is to survey Jupiter's complex auroral regions at both poles. Using the first concurrent radio‐UV aurora observations of both north and south hemispheres during three closest approaches to the planet, we found that the source locations of Jovian auroral radiation at the kilometer wavelengths (broadband kilometric radiation) are magnetically connected to regions of bright UV emissions on the main auroral oval. For some events, the UV auroral intensity positively correlates with broadband kilometric radio intensity. Juno's vantage point of Jovian auroras at radio and UV wavelengths yields a better understanding of the auroral processes at different altitudes. Key Points: First simultaneous observations of Jovian broadband kilometric radio source footprints and ultraviolet auroras were carried out using Juno Jovian broadband kilometric radio source footprints correspond to the UV main oval locations Link of Jovian radio intensity during Juno's near‐source crossing with both brightness and color ratio of the UV main oval was investigated